Integrasi komponen pengendalian hama penggerek ubi jalar (Cylas formicarius Fab.) (Coleoptera: Curculionidae) - Yusmani Prayogo; Nurul Setyanignsih; Didik Hariyono; Nur Edy Suminarti (Perhimpunan Entomologi Indonesia, 2022)
Sweetpotato weevil Cylas formicarius Fabricius is major obstacle in increasing of sweet potato production in various countries. Tuber damage due to C. formicarius causes yield loss up to 80%. This study aims to examine the integration control of C. formicarius in entisol, each control combination was composed of various components. The control integration was composed of various components of synthetic insecticide, application of entomopathogenic fungus Beauveria bassiana, weeding, turning of the stems, heap up, and cover mounds using plastic mulch. The study used a randomized block design, each treatment was repeated five times. The research was conducted at Kendalpayak experimental station from May to September 2017. The result showed that P5 with B. bassiana application five times, addition of 3 t/ha organic fertilizer, cover mounds by plastic mulch was most effective in suppressing of C. formicarius in endemic entisol. The tuber weight at control combination (P5) was reached 23 t/ha or 56% higher than control combination of farmer cultivation (P1) was only 10 t/ha. The entisol land with an alluvial structure cracks easily during in the dry season, so that adults to penetrate the base of tubers and lay their eggs. The results of this study indicate that control combination of P5 can be recommended as a innovation control technology of C. formicarius in endemic entisol.